Warming affects leaf light use efficiency and functional traits in alpine plants: evidence from a 4-year in-situ field experiment - Zhou, Zijuan; Su, Peixi; Yang, Jianping; Shi, Rui; Ding, Xinjing (Frontiers in Plant Science, 2024)
Light use efficiency (LUE) is a crucial determinant of plant productivity, while leaf functional traits directly affect ecosystem functions. However, it remains unclear how climate warming affects LUE and leaf functional traits of dominant species in alpine meadows. We conducted a 4year in-situ field warming experiment to investigate the eco-physiological characteristics for a dominant species (Elymus nutans) and a common species (Potentilla anserina) on the Tibetan Plateau. To investigate the impacts of warming on LUE and leaf functional traits of alpine plants, we conducted a 4-year in-situ warming simulation experiment. We measured leaf traits, photosynthesis and fluorescence characteristics, as well as soil physical-chemical properties related to plant eco-physiological characteristics for a dominant species (E. nutans) and a common species (P. anserina) on the Tibetan Plateau. The leaf traits, photosynthesis and fluorescence characteristics were measured, along with the soil physical-chemical properties associated with the two species. Experimental warming increased the leaf LUE, Following a four-year in-situ warming experiments, we observed an increase in leaf LUE, maximum photochemical efficiency, non-photochemical quenching, relative water content, and specific leaf area, for both species and soil respiration rate for both species. However, there was a decrease in leaf and soil element content. Different species exhibit varying adaptability to warming. The photosynthetic rate, stomatal conductance, transpiration rate, total water content, and specific leaf volume of E. nutans were significantly increased by the warming. Increasing temperature significantly increased the photosynthetic rate, stomatal conductance, transpiration rate, total water content, and specific leaf volume of E. nutans; however, all these traits exhibited an opposite trend in P.anserina. Warming has a direct negative impact on leaf LUE and an indirectly enhances LUE through its effects on leaf traits. The impact of warming on plant photosynthetic capacity is primarily mediated by soil nutrients and leaf traits. These results indicate that the two different species employ distinct adaptive strategies in response to climate change, which are related to